33.2k views
0 votes
Answer this question -5(x+3)=x-6+2(3x+3)

2 Answers

4 votes
The answer is x= -5/4
Answer this question -5(x+3)=x-6+2(3x+3)-example-1
User Tarulen
by
5.4k points
5 votes

In this question, you're solving for x.

Solve for x:

-5(x+3) = x - 6 + 2(3x+3)

Use distributive property:

-5(x+3) = x - 6 + 2(3x+3)

-5x - 15 = x - 6 + 2(3x+3)

-5x - 15 = x - 6 + 6x + 6

Combine like terms:

-5x - 15 = 7x

Subtract 7x from both sides

-12x - 15 = 0

Add 15 to both sides

-12x = 15

Divide both sides by -12

x = -15/12

Simplify by dividing both sides by 3

x = -5/4

Answer:

x = -5/4

User Julien Deniau
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.